STRATEGI BERTAHAN HIDUP (LIFE SURVIVAL STRATEGY) MASYARAKAT MISKIN DI DESA LOPOK BERU KABUPATEN SUMBAWA - Suprianto, S; Hidayati, Raomatul (Jurnal Ekonomi & Bisnis, 2024)
This study was conducted on the life survival strategy of poor society in Lopok Beru Village. The type of this study was descriptive which aims to explain the description of the survival strategies of poor society in Lopok Beru Village. The type of data used in this study was qualitative data obtained directly from primary sources using a research instrument in the form of interview guidelines. The primary sources who were the informants in this study were the Village Head, Hamlet Head, Neighborhood Association (RT), Citizens Association (RW), Religious Leaders, and the poor society in Lopok Beru. The data that has been collected will then be analyzed using Miles and Huberman's qualitative data analysis techniques, including data reduction, data display, and drawing conclusions/verification. The results of study showed that poor society in Lopok Beru Village generally had a relatively low level of education. The poor society in Lopok Beru Village mostly work as farm laborers with relatively small and uncertain incomes so that they often experience difficulties and deficiencies in meeting the daily needs of their families. Therefore, poor society in Lopok Beru Village carry out various strategies in order to survive economic pressures. Some of the strategies they apply include active strategies, passive strategies, and network strategies. Active strategies, including doing side jobs, and involving family members in work. Passive strategy was carried out by getting used to a frugal lifestyle. Networking strategy is carried out by asking for help from relatives or neighbors when in an urgent situation.